A Scoping Review and Narrative Synthesis Comparing the Constructs of Social Determinants of Health and Social Determinants of Mental Health: Matryoshka or Two Independent Constructs? - Handerer, Fritz; Kinderman, Peter; Shafti, Matina; Tai, Sara (Frontiers in Psychiatry, 2022)
Background: Many health research policies invoke the construct of Social Determinants of Health, and more recently the construct of Social Determinants of Mental Health. While frequently referred to in the literature, it is unclear how these constructs relate to each other. Some commentators conceptualise the Determinants of Mental Health as a subgroup of the Determinants of general Health and others describe the Determinants of Mental Health as an autonomous construct. The current review investigates the relationship between both constructs. Methods: Comprehensive literature searches were conducted for both constructs separately within seven electronic databases. A template analysis was conducted to compare the conceptualisations of the Social Determinants of Health and the Social Determinants of Mental Health. Results: Of 4250 search results, we included 50 papers (25 for each construct) that fulfilled our inclusion criteria in a narrative synthesis. Discussions of the Social Determinants of both general and Mental Health listed the same determinants. Both constructs were conceptualised on multiple levels and factors. Stress and health behaviour were also described as mediators for both constructs. The constructs differed, however, with respect to two components of their aetiologies and epistemologies. First, the causal mechanisms invoked for the Determinants of general Health followed predominantly direct pathways, in contrast to indirect pathways for the Social Determinants of Mental Health. Second, the Social Determinants of Mental Health were reported to influence mental health mediated through individuals’ perceptions and appraisal processes. Appraisal processes were considered of far less relevance in the construct of Social Determinants of Health. Conclusion: The constructs of Social Determinants of Health and Social Determinants of Mental Health align in many respects but differ on important aetiological and epistemological grounds. Similar social factors are considered important, but whereas physical health conditions are primarily conceptualised to be driven by objective realities, mental health is explained mainly in terms of perception of these realities. This differentiation between physical and mental health is in line with a modern understanding of mind-body-dualism, the naturalistic dualism after Chalmers. Differentiating the Social Determinants of Mental Health from the Social Determinants of Health might bear relevance for policy making and research.